2012
DOI: 10.1177/1403494812460347
|View full text |Cite
|
Sign up to set email alerts
|

Parenting stress and emotional wellbeing in mothers and fathers of preschool children

Abstract: Fathers reported significantly more social isolation, but less role restriction, incompetence and state anxiety than mothers. The SPSQ together with GHQ-28 and STAI-X1 allow a targeted screening aimed at contrasting parents who experience reduced emotional wellbeing with those who struggle with stress directly related to their parenting role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
68
0
28

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 27 publications
12
68
0
28
Order By: Relevance
“…There is now growing recognition that depressive symptoms, which include fear and anxiety, in both men and women after the birth of a child, predict parental stress. For example Skreden and co-workers showed a correlation between psychological wellbeing, somatic symptoms and parenting stress (Skreden et al, 2012). Further to this, a very recent Swedish study reported that fathers with depressive symptoms often rated their child as more difficult, both three months and 18 months after birth (Kerstis et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…There is now growing recognition that depressive symptoms, which include fear and anxiety, in both men and women after the birth of a child, predict parental stress. For example Skreden and co-workers showed a correlation between psychological wellbeing, somatic symptoms and parenting stress (Skreden et al, 2012). Further to this, a very recent Swedish study reported that fathers with depressive symptoms often rated their child as more difficult, both three months and 18 months after birth (Kerstis et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…More recent studies, primarily from Sweden, have found that mothers and fathers experience parental stress in different areas. Mothers are more likely to experience stress related to their role as a parent and their relationship with their spouse/partner while men are more likely to experience parental stress in regards to social isolation (Jackson et al, 2007;Skreden et al, 2012;Tommiska et al, 2002;Widarsson et al, 2012). Some studies that included or focused on fathers found that changes in the marital/partner relationship were associated with more parenting stress for fathers than mothers (Deater-Deckard & Scarr, 1996).…”
Section: Introductionmentioning
confidence: 92%
“…These relationship difficulties, in conjunction with their adolescent children's challenging behaviors may foster parents' perceptions that the demands of parenting exceed their physical, economic, and emotional resources to meet those demands (Deater-Deckard 1998). Third, parents who experience high levels of parenting stress have poorer psychological wellbeing (Skreden et al 2012), exhibit fewer positive parenting behaviors (Crnic and Low 2002), and are less able to implement parenting interventions than other parents (e.g., Kazdin and Whitley 2003). Acquisition of positive parenting skills and higher sense of parenting competence improves intervention impact on adolescent internalizing and externalizing behavior (Compas et al 2010;Deković et al 2012).…”
mentioning
confidence: 96%